Distribución de los esfuerzos en tramos protésicos fijos de cinco unidades con pilar intermedio: análisis biomecánico utilizando un modelo de elementos finitos (2011)
ABSTRACT: The purpose of this study is to establish the mechanical behavior between rigid and non-rigid fixed dental prosthesis of five units with an intermediate abutment using the finite element analysis (FEA). Methods: a five unit rigid model with 124.469 nodes and 76.215 elements and a non-rigid model with 125.130 nodes and 77.396 elements were designed. It consisted of trabecular bone, cortical bone, periodontal ligament, pulp, dentine, root, resinous cement, metal ceramic crowns and tube-lock adjustment (Sterngold®, Implamed Attleboro MA). The fixed dental prosthesis included a central incisor, lateral incisor, canine, first and second upper premolars. A force of 200 N was applied with an oblique and vertical direction. The variables included in the model were modulus of elasticity, Poisson’s ratio and non-rigid adjustment. Von Misses stresses, main, maximum and minimum, were calculated for each group. Results and conclusions: the analysis of the mechanical behavior indicated that the rigid fixed dental prosthesis showed a better distribution of the stresses in comparison with the non-rigid model. The behavior of each group indicated that the rigid model transmitted less stress to the underlying root and bone. The indication to use an adjustment would not be justified according to the results of this study.